Development of Differentiated Instruction-Based LKS to Improve Grade VIII Students' Understanding of SPLDV Material at SMPN 2 Enrekang - Burhan Burhan; Putriani Putriani; Rustiani Rustiani (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to develop Student Worksheets (LKS) based on Differentiated Instruction (DI) to improve the understanding of eighth grade students on the material of Two-Variable Linear Equation Systems (SPLDV) at SMPN 2 Enrekang. The method used is research and development (R&D) with the ADDIE model which includes five steps: needs analysis, product design and development, implementation, evaluation, and data analysis. The results of the study indicate that the application of DI-based LKS can improve students' understanding of SPLDV material, as evidenced by a significant increase in pre-test and post-test results. DI-based LKS provides questions with a level of difficulty that is adjusted to the student's abilities, so that each student can learn according to their abilities. Thus, this study suggests the use of DI-based LKS for other mathematics materials as an effort to improve the quality of learning and student learning outcomes.